Biological activities of Annona montana Macfad extracts - Ana Isabel Giraldo Rivera; Gloria Edith Guerrero Álvarez (Universitas Scientiarum)
Annona montana Macfad is a fruit species of the Annonaceae family. In this study, the phytochemical potential of A. montana seeds was investigated. Ethanol and hexane extracts from seeds were evaluated for cytotoxicity and insecticidal activity, phenolic content, and antioxidant capacity. The latter being related to free radical scavenging activity assay (DPPH) and ferric reducing power (FRAP). Exposing Artemia salina to both seed extract types reveled their high toxicity with a median lethal concentration (LC50) of < 10 μg mL-1. Further A. montana seed insecticidal activity was evaluated against Thrips tabaci L., revealing that the most promising treatments were observed for a concentration of 100 mg L-1 in both extracts. The ethanol extract resulted in a mortality of 67.5 % and the hexane extract in a 53.3 % mortality. The ethanolic extract of A. montana seeds showed the highest total phenolic content: 297.38 mg GAE/100 g of dried extract and 192.66 mg TE/100 g, and 385.46 mg TE/100 g for DPPH and FRAP, respectively. The chemical characterization of both extracts by high performance liquid chromatography (HPLC) revealed the presence of acetogenins. The results obtained idicate that the A. montana extracts are a promising source of compounds with insecticidal activity.